Adolescence and Polycystic Ovary Syndrome: current concepts on diagnosis and treatment - Motta, Alicia Beatriz (2015)
Background: Adolescence is a time characterized by changes in reproductive hormones and menstrual patterns, which makes it difficult to diagnose Polycystic Ovary Syndrome (PCOS) in this population. The diagnosis of PCOS has great physical and psychosocial impact in the young person. Despite the importance of a diagnosis of PCOS at adolescence, data available are limited. Aims: This review focuses on analyzing markers of PCOS diagnosis and possible treatments in adolescence. Results: Although during adolescence diagnosis criteria of PCOS overlap with physiological changes including clinical manifestations of hyperandrogenism (acne and hirsutism,), oligo/amenorrhea, anovulation and ovarian microcysts, there is agreement that irregular menses and hyperandrogenemia should be used to diagnose PCOS in this population. Moreover, considering that PCOS phenotype could change through the reproductive age and that adolescents display heterogeneous ovarian morphology, it has been proposed that diagnosis of PCOS should be confirmed after the age of 18. The first-line treatment for menstrual irregularity and hirsutism are oral contraceptive pills and for obesity and metabolic abnormalities are lifestyle changes. Insulin-sensitizer drugs, such as metformin, may be added to the treatment in the presence of metabolic alterations. Antiandrogen drugs may also be associated for treating moderate to severe hirsutism. Conclusions: During adolescence, physiological changes overlap with signs and symptoms of PCOS; thus the diagnosis criteria should be carefully considered. Regarding the treatment of adolescents with PCOS, non-pharmacological interventions include lifestyle changes. Pharmacological treatments comprise oral contraceptive pills, antiandrogens and metformin, used isolated or combined.